Carbohydrate intake targets for athletes: Grams or percent? - Burke, L. (Sportscience)
On carbohydrate intake goals for the athlete and the used terminology. (An excerpt from Peak Performance: Training and Nutritional Strategies for Sport, by John Hawley and Louise Burke, published by Allen and Unwin)